Characteristics and antioxidant activity of royal lotus pollen, butterfly pea flower, and oolong tea kombucha beverages - Narathip Wongthai (2022)
Kombucha is a fermented functional tea beverage that is prepared by inoculating a microbial consortium comprising acetic acid bacteria and yeast into sweetened black tea and incubating it under aerobic conditions. In this study, kombucha beverages of royal lotus pollen (Nelumbo nucifera), butterfly pea flowers (Clitoria ternatea), and oolong tea (Camellia sinensis) leaves were prepared via fermentation with a kombucha consortium containing acetic acid bacteria and yeast for a period of 20 days. The amounts of acetic acid and ethanol in royal lotus pollen kombucha (LK), butterfly pea flower kombucha (BK), and oolong tea kombucha (OK) samples gradually increased after fermentation. In addition, the total phenolic contents (TPCs), total flavonoid contents (TFCs), 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) free radical scavenging capacities, and 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging capacities of all the kombucha beverages gradually increased after fermentation; the beverages exhibited the highest antioxidant capacity on day 20 of fermentation. The kombucha beverages from butterfly pea flowers and oolong tea leaves significantly inhibited hydrogen peroxide-induced reactive oxygen species (ROS) production by increasing the synthesis of antioxidant enzymes such as catalase, manganese superoxide dismutase (Mn-SOD), glutathione reductase (GRe), glutathione peroxidase-1 (GPx-1), and heme oxygenase-1 (HO-1) in human embryonic kidney-293 (HEK-293) cells. Therefore, the consumption of these antioxidant-rich kombucha beverages can reduce the risk of oxidative stress, which is the cause of many diseases.